The L1 cell adhesion molecule constrains dendritic spine density in pyramidal neurons of the mouse cerebral cortex - Murphy, Kelsey E.; Wade, Sarah D.; Sperringer, Justin E.; Mohan, Vishwa; Duncan, Bryce W.; Zhang, Erin Y.; Pak, Yubin; Lutz, David; Schachner, Melitta; Maness, Patricia F. (Frontiers in Neuroanatomy, 2023)
A novel function for the L1 cell adhesion molecule, which binds the actin adaptor protein Ankyrin was identified in constraining dendritic spine density on pyramidal neurons in the mouse neocortex. In an L1-null mouse mutant increased spine density was observed on apical but not basal dendrites of pyramidal neurons in diverse cortical areas (prefrontal cortex layer 2/3, motor cortex layer 5, visual cortex layer 4. The Ankyrin binding motif (FIGQY) in the L1 cytoplasmic domain was critical for spine regulation, as demonstrated by increased spine density and altered spine morphology in the prefrontal cortex of a mouse knock-in mutant (L1YH) harboring a tyrosine (Y) to histidine (H) mutation in the FIGQY motif, which disrupted L1-Ankyrin association. This mutation is a known variant in the human L1 syndrome of intellectual disability. L1 was localized by immunofluorescence staining to spine heads and dendrites of cortical pyramidal neurons. L1 coimmunoprecipitated with Ankyrin B (220 kDa isoform) from lysates of wild type but not L1YH forebrain. This study provides insight into the molecular mechanism of spine regulation and underscores the potential for this adhesion molecule to regulate cognitive and other L1-related functions that are abnormal in the L1 syndrome.